Sector dynamics and demographics of top R&D firms in the global economy - Pietro Moncada-Paternò-Castello (European Commission, Joint Research Centre (JRC), 2016)
This paper investigates the sectoral dynamics of the major economies during the last decade through the lens of the top 1000 R&D investors worldwide and looks at how firms' demographics are related to sector distribution. In doing so, it contributes to the literature on the EU corporate R&D intensity gap as well as on that on industrial dynamics. Contrary to the common understanding, the results show that in the EU the distribution of R&D among sectors has changed more than in the USA, which has experienced a shift mainly towards ICT-related sectors. In both the EU and the USA the pace of R&D change is slower than in the emerging economies. Furthermore, the EU has been better able than the USA and Japan to maintain its world share of R&D investment. Even more interestingly, the results show that age is strongly related to the sector (and dominant technology) in which firms operate. This suggests that focusing on sector (technological) dynamics could be even more relevant from a policy perspective than focusing only on young leading innovators. In fact, EU firms are less able to create or enter new high-tech sectors in a timely way and fully exploit the growth opportunities offered by first mover advantages.
Keywords: O30; O32; O38; O57; 330; Corporate R&D; sector dynamics; firms' age; EU R&D intensity deficit